Optimalisasi Pemasaran Digital Kombucha Kulit Nanas Bukit Merdeka Kabupaten Kutai Kartanegara - Ananda Putra Agung; Qurratu Aini; I Putu Gede Widiarta; Amalina Nur Wahyuningtyas (CV. Era Digital Nusantara, 2025)
Bukit Merdeka Village, located in Samboja Subdistrict, Kutai Kartanegara Regency, holds great potential in developing processed products based on pineapple. However, product marketing remains a major challenge, particularly in terms of utilizing digital technology. This community service program aimed to enhance the capacity of the local women’s group (Ibu PKK) in processing pineapple peels into kombucha beverages and marketing the products through digital platforms. A total of 15 participants, all members of the Ibu PKK group, actively participated in the activity. The method used was direct practice and small group discussions. The results showed a significant improvement for understanding of how to use digital platforms as promotional tools. In addition, the participants showed high enthusiasm for developing home-based businesses by utilizing organic waste such as pineapple peels. This program demonstrates the potential of combining local resource utilization with digital marketing skills to empower community-based entrepreneurship.